PENGARUH PENERAPAN SAFETY PATROL TERHADAP KEPATUHAN PEMAKAIAN ALAT PELINDUNG DIRI (APD) DI PT X - Bayu Sela Priyatna; Idham Latif; Disya Hana Rahayu (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Workers' compliance in using personal protective equipment (PPE) in industry, especially those with high risk, requires a commitment to occupational safety and health (K3) from the company, management, and workers. Compliance is a form of behavior that can be influenced by internal factors. Compliance with the use of PPE is a specific safety behavior towards the object of the work environmen. This research method uses Literature Review or literature study with the Systematic Review method. The results of the collection of articles that match the inclusion criteria in this study were 7 articles, which were obtained through Google Scholar by using the keywords safety patrol and the use of PPE. The results of a literature study on the effect of the application of safety patrols on compliance with the use of personal protective equipment were obtained as many as 5 of 7 articles which stated that there was an influence between the application of safety patrols on compliance with the use of PPE. The conclusion of this study is that based on research conducted using the literature study method, there are two articles that say there is no influence between a good K3 program in which there is a Safety Patrol program with worker compliance in the use of PPE.